Effective clinical supervision of allied health professionals: a mixed methods study - David A. Snowdon; Michelle Sargent; Cylie M. Williams; Stephen Maloney; Kirsten Caspers; Nicholas F. Taylor (BMC, 2019)
Abstract Background Clinical supervision is recommended for allied health professionals for the purpose of supporting them in their professional role, continued professional development and ensuring patient safety and high quality care. The aim of this mixed methods study was to explore allied health professionals' perceptions about the aspects of clinical supervision that can facilitate effective clinical supervision. Methods Individual semi-structured interviews were conducted on a purposive sample of 38 allied health professionals working in a metropolitan public hospital. Qualitative analysis was completed using an interpretive description approach. To enable triangulation of qualitative data, a quantitative descriptive survey of clinical supervision effectiveness was also conducted using the Manchester Clinical Supervision Scale (MCSS-26). Results Three main themes emerged from qualitative analysis: Allied health professionals reported that clinical supervision was most effective when their professional development was the focus of clinical supervision; the supervisor possessed the skills and attributes required to facilitate a constructive supervisory relationship; and the organisation provided an environment that facilitated this relationship together with their own professional development. Three subthemes also emerged within each of the main themes: the importance of the supervisory relationship; prioritisation of clinical supervision relative to other professional duties; and flexibility of supervision models, processes and approaches to clinical supervision. The mean MCSS-26 score was 79.2 (95%CI 73.7 to 84.3) with scores ranging from 44 to 100. MCSS-26 results converged with the qualitative findings with participants reporting an overall positive experience with clinical supervision. Conclusions The factors identified by allied health professionals that influenced the effectiveness of their clinical supervision were mostly consistent among the professions. However, allied health professionals reported using models of clinical supervision that best suited their profession's role and learning style. This highlighted the need for flexible approaches to allied health clinical supervision that should be reflected in clinical supervision policies and guidelines. Many of the identified factors that influence the effectiveness of clinical supervision of allied health professionals can be influenced by health organisations.